IMPLEMENTASI UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN (Kasus Perlindungan Hak Pekerja/Buruh Perempuan Pada Sektor Garmen Di Kota Semarang) - Ernita Manik (Journal of Politic and Government Studies, 2013)
Abstract:Women are often depicted with a weak creature because she has multiple functions, reproductive functions and social functions, which related to reproductive function of menstruation, pregnancy, breastfeeding and childbirth. However, at the present time a lot of women who participated in the working world, an increasing number of women workers in the garment sector in particular makes female labor protection related reproductive function. Labor laws that essentially provides protection against labor but in fact common irregularities and violations primarily related submissions leave menstruation, pregnancy, childbirth, miscarriage, and breast-feeding because the company considers such leave will inhibit the production of the company up to a lot of labor do not get their due in the world of work. This study used qualitative research type is descriptive and aims to provide a systematic overview of the events. Techniques for data collection using interviews and observation techniques, while this study can be used to acquire a broad knowledge of the research subject. These results indicate that the implementation of Law No. 13 of 2003 on Manpower is still not optimal because there are many cases of violations of the rights of women workers related submissions leave menstruation, pregnancy, childbirth, miscarriage, and breast-feeding. This was due to the lack of effective communication from the government and firms to labor than that sanctions are not effective because many violations committed by the company but received no sanction in accordance with existing laws. That the implementation of labor law can work well it is necessary to the government's role in overseeing the company in violation and give strict punishment for violators besides the need for effective communication to be one step in optimizing the application of the Act in particular labor protection of women.